Key drivers of profit sharing rates in mudharabah time deposits: Evidence from Islamic banks in Indonesia - Latifah Muliji; Erni Panca Kurniasih; Yarlina Yacoub (Universitas Sebelas Maret, 2025)
People who save their funds tend to choose products that provide high profits. Profit sharing on Islamic bank deposit products is a unique attraction for people to save funds. Bank external and internal factors are needed in determining the amount of profit sharing. This study aims to identify the variables that affect the amount of profit sharing from deposits in the mudharabah system. With a quarterly observation period spanning from 2013 to 2022, the sample for this study consists of all Sharia commercial banks registered with the OJK. The error correction model (ECM) is the technique employed. Based on the long-term ECM test results, non-performing financing and interest rates partially have a positive and significant effect. The exchange rate has a negative and significant effect. In contrast, the liquidity ratio, inflation, and GDP per capita have no effect. In the short-term ECM test results, non-performing financing has a significant positive effect. In contrast, liquidity ratio, inflation, exchange rate, interest rate, and GDP per capita have no effect. These findings demonstrate that while the non-performing finance variable consistently impacts over the long and short-terms, the liquidity ratio, inflation, and GDP per capita variables consistently have no effect.